Associations of serum uric acid trajectories with hypertension risk: exploring differences between age groups - Li, Mao; Yu, Bin; Pan, Jia; Dong, Chaohui; Zeng, Honglian; Yang, Shujuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHyperuricemia is a recognized predictor of hypertension. However, the consistent link between elevated serum uric acid (SUA) levels and hypertension risk across different age groups, especially in males, remains a subject of debate. This study aimed to examine the association between SUA trajectories and the risk of new-onset hypertension, focusing on age-group disparities.MethodsWe conducted a longitudinal study of 4,221 male employees from Southwestern China, initially free of hypertension, over a 4-year period (2018–2021). All employees underwent annual physical examinations each year. Incident hypertension was defined as newly detected blood pressure ≥140/90 mmHg, or the initiation of anti-hypertensive medication. We employed group-based trajectory modeling to identify the trajectory patterns of SUA levels over the study period. Logistic regression was used to assess the association between these SUA trajectories and the risk of developing hypertension. Additionally, subgroup analyses were conducted by stratifying participants into young (<45 years) and middle-aged (≥45 years) groups, with sensitivity analyses conducted using additional cutoffs of 40 and 50 years.ResultsFour distinct SUA trajectories were identified: low (21.18%), moderate-low (45.44%), moderate-high (28.26%), and high (5.12%). The 4-year cumulative incidence of hypertension was 13.2%. Compared to the low SUA trajectory, the high SUA trajectory was independently associated with an increased risk of developing hypertension (OR = 2.22, 95% CI 1.43–3.43). The risk of developing hypertension increased significantly with higher SUA trajectories (P for trend = 0.003), and this dose-response relationship was modified by age (P for interaction = 0.026). In male employees under 45 years, the high SUA trajectory was associated with a higher risk of hypertension (OR = 1.78, 95% CI 1.04–3.07) compared to the low SUA trajectory, while no significant association was found in male employees over 45 years (OR = 2.22, 95% CI 0.89–5.33). Sensitivity analyses showed a significant association in males <40 years (OR = 2.17), a borderline association in those aged 40–49 (OR = 2.07, P = 0.053), but none in those ≥50 (OR = 1.22).ConclusionPersistently high SUA levels may elevate hypertension risk in males, particularly younger individuals. Age-specific management of SUA may be necessary for hypertension prevention, with early intervention in young men likely yielding greater benefits than in middle-aged men.